Terrestrial carbon balance in a drier world: the effects of water availability in southwestern North America. (15th February 2016) - Biederman, Joel A.; Scott, Russell L.; Goulden, Michael L.; Vargas, Rodrigo; Litvak, Marcy E.; Kolb, Thomas E.; Yepez, Enrico A.; Oechel, Walter C.; Blanken, Peter D.; Bell, Tom W.; Garatuza‐Payan, Jaime; Maurer, Gregory E.; et al.
Abstract: Global modeling efforts indicate semiarid regions dominate the increasing trend and interannual variation of net CO2 exchange with the atmosphere, mainly driven by water availability. Many semiarid regions are expected to undergo climatic drying, but the impacts on net CO2 exchange are poorly understood due to limited semiarid flux observations. Here we evaluated 121 site‐years of annual eddy covariance measurements of net and gross CO2 exchange (photosynthesis and respiration), precipitation, and evapotranspiration (ET) in 21 semiarid North American ecosystems with an observed range of 100 – 1000 mm in annual precipitation and records of 4–9 years each. In addition to evaluating spatial relationships among CO2 and water fluxes across sites, we separately quantified site‐level temporal relationships, representing sensitivity to interannual variation. Across the climatic and ecological gradient, photosynthesis showed a saturating spatial relationship to precipitation, whereas the photosynthesis–ET relationship was linear, suggesting ET was a better proxy for water available to drive CO2 exchanges after hydrologic losses. Both photosynthesis and respiration showed similar site‐level sensitivity to interannual changes in ET among the 21 ecosystems. Furthermore, these temporal relationships were not different from the spatial relationships of long‐term mean CO2 exchanges with climatic ET. Consequently, a hypothetical 100‐mm change in ET, whether short term or long term, was predicted to alter net ecosystem production (NEP) by 64 gCm −2 yr −1 . Most of the unexplained NEP variability was related to persistent, site‐specific function, suggesting prioritization of research on slow‐changing controls. Common temporal and spatial sensitivity to water availability increases our confidence that site‐level responses to interannual weather can be extrapolated for prediction of CO2 exchanges over decadal and longer timescales relevant to societal response to climate change.